The impacts of the COVID-19 pandemic and responses from various policy actors in the Czech Republic and Slovakia in 2020: An introduction to a special issue - Daniel Klimovský; Juraj Nemec (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Hundreds of thousands of articles related to COVID-19 have been published worldwide, and many of them have focused on public administration and public policy aspects related to this pandemic. Certainly, the general lack of relevant knowledge and necessary experience for a robust governance strategy and evidence-based policy-making became a global problem in 2020. This is certainly the case for all countries of the Central and Eastern European region, including the Czech Republic and Slovakia. This gap in research perspectives needs to be filled because of the enormous public policy challenges raised due to the COVID-19 pandemic. SciPap is an international academic journal of regional importance, and this special issue aims to contribute some answers to present research shortcomings and the lack of inputs for evidence-based policy-making. More precisely, this special issue is focused on public policies and responses of various actors to the COVID-19 pandemic in the Czech Republic and Slovakia in 2020.
Keywords: E61; H12; H72; H75; 330; Czech Republic; Public Administration; Slovakia; Public Policy; Covid-19; Pandemic